Model inventarisasi informasi geospasial air tanah bebas menggunakan web gis - Sejati, Sadewa Purba; Setiawan, Wahyu Dwi (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2023)
Several countries have placed groundwater spatial information inventories in a significant position in groundwater management. However, this effort has not been found in Indonesia. This is probably due to limited references. This study aims to determine the spatial information of groundwater as a basis for inventory. The research also aims to identify the capabilities of Arc GIS online as a medium for inventorying groundwater spatial information. As a preliminary study, Sitimulyo Village, Bantul Regency, Special Province of Yogyakarta was used as the study area. Data was collected through field surveys. Spatial interpolation was used for data analysis. Based on the results of the study, it is known that the free groundwater in the majority of the research area is 6.7 to 9.5 meters deep. Studies on electrical conductivity, temperature, and alkalinity also indicate that groundwater quality is good. Arc GIS online can be used as a medium for inventorying groundwater information. Easy accessibility, supported by simple data management and updating, is the advantage of Arc GIS online.